GAMBARAN KESIAPAN MENARCHE SISWI DI SD 2 DALUNG - ida arimurti sanjiwani; I Gusti Ayu Pramitaresthi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
The transition from childhood to adolescence will experience puberty which is characterized by sexual maturity and physical changes and menarhce. The readiness to face menarche has an impact on the reactions of young women when their first menstrual period arrives. This study aims to determine the level of readiness of students in undergoing menarche. This research was a quantitative descriptive study with an observational approach. This study used a stratified random sampling technique to 65 female students at SD 2 Dalung. The data were obtained by using a menarche readiness questionnaire with the results showing that the level of readiness of students in facing menache was in the low category (5,34). It is suggested that an approach and education be carried out from both families and schools to improve students' readiness to face menarche.